The Golden Generation and the wasted generations: Romania and the world cup. (3rd October 2022) - Adam, Robert
ABSTRACT: This paper examines the relationship between Romania and the World Cup and finds this relationship to be influenced by the achievements of the 1990s. That decade, an exception in a rather poor World Cup history of Romania, set too high expectations for the Romanian football fans from the subsequent generations. A division was created between the so called 'Golden Generation', which in fact was nowhere near winning a trophy, and the following ʿwasted generationsʾ. The myth of the Golden Generation sought materialization in the power struggles within Romanian football, yet with little success. It also explores Romania's most significant football rivalries, with neighbouring countries, and their cultural and political causes. The perception of issues in the 2018 Russia World Cup (dual-nationality players, French team's 'African-ness', political instrumentalization) was impacted by specific factors (mistrust of minorities, ethnic conception of the nation), yet the 'political' dimension of the tournament was all but wasted on the Romanian audience.